Unprecedented recurrence of carpal tunnel syndrome by metaplastic synovial cyst in the carpal tunnel - Karaytug, Kayahan (Acta Orthop Traumatol Turc, 2019)
Metaplastic synovial cyst (MSC) is a benign cystic lesion observed after surgical intervention and recurrent skin trauma. Because of its rarity, the etiology is not fully understood. The most emphasized etiologic factors are recurrent surgical procedures and cutaneous pathologies, which cause cutaneous fragility and abnormal wound formation. In the literature, MSC is exemplified as a mass that can be observed by the naked eye and palpated. All patients had a history of previous surgical procedures in the area. In the present case, we report a 48 -year-old woman with recurrent carpal tunnel syndrome due to a MSC. This report showed that MSC can be detected at deeper locations than the regions described in the literature. To our knowledge, this is the first report of MSC causing carpal tunnel syndrome recurrence. It is thought that previous operations are the most important etiologic factor in MSC occurrence.